2019
DOI: 10.1093/ejo/cjz049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro-osteoperforation on the rate of orthodontic tooth movement—a systematic review and a meta-analysis

Abstract: Background The micro-osteoperforation can be used to increase the rate of tooth movement, simplify complex orthodontic movements, and also help adjust the anchorage but there are conflicting reports on the effectiveness and adverse effects of this intervention. Objectives The aim of our systematic review and meta-analysis was to evaluate the effects of micro-osteoperforation on the rate of tooth movement in patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 36 publications
3
43
0
5
Order By: Relevance
“…For comparison, MOP alone ranked fifth for the included adjunctive therapies and was efficacious in increasing the rate of OTM only in the first month of treatment by 0.35 mm/month. This finding is similar to a recent meta‐analysis that found a small and clinically insignificant increase in OTM (0.45 mm/month) after the use of MOP 72 . Another more recent systematic review and meta‐analysis that concluded that a single application of MOPs does not accelerate OTM 73 .…”
Section: Discussionsupporting
confidence: 87%
“…For comparison, MOP alone ranked fifth for the included adjunctive therapies and was efficacious in increasing the rate of OTM only in the first month of treatment by 0.35 mm/month. This finding is similar to a recent meta‐analysis that found a small and clinically insignificant increase in OTM (0.45 mm/month) after the use of MOP 72 . Another more recent systematic review and meta‐analysis that concluded that a single application of MOPs does not accelerate OTM 73 .…”
Section: Discussionsupporting
confidence: 87%
“…These findings demonstrate the effectiveness of the piezocision procedure in accelerating the canine retraction rate with a statistically significant difference. Similar results regarding accelerating tooth movement were made in other studies [12,16,17,36,[45][46][47] but differed in the effect size. Interestingly, Fu et al [17] reported similar results in their meta-analysis, but they included five different surgical interventions, one of them was in combination with laser and pooled heterogeneous methodological and clinical studies in the same meta-analysis.…”
Section: Summary Of Evidencesupporting
confidence: 82%
“… 23 In a recently published meta-analysis, MOPs have been stated to increase the amount of canine retraction at the rate of 0.45 mm/month, and this change was found to be statistically significant. 24 In our previously published study, we have reported that 3 MOPs with a 5-mm depth could accelerate canine movement significantly at the rate of 1.76 ± 0.66 mm/month, while the rate in the control group was 1.36 ± 0.81 mm/month (with a mean increase of 0.40 mm/month). 18 In the current study, the difference in the mean rate of canine retraction between the experimental (1.25 mm) and control groups (0.88 mm) was 0.37 mm, indicating a similarity with both the literature and our previous data.…”
Section: Discussionmentioning
confidence: 74%